2013
DOI: 10.1108/mrr-06-2012-0141
|View full text |Cite
|
Sign up to set email alerts
|

Is the Indian stock market cointegrated with other Asian markets?

Abstract: PurposeThe purpose of this paper is to investigate the linkages between Indian stock markets with other Asian stock markets namely, Hong Kong, Indonesia, Japan, South Korea, Malaysia, Taiwan and China. Such a study is particularly important because if the level of integration among the markets is high, then investing in different markets will not generate long term gains from portfolio diversification or reduction in risk.Design/methodology/approachThe paper applies unit root test in the presence of endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 59 publications
0
6
1
Order By: Relevance
“…It was seen in his paper that shocks in US had impact on Bangladesh, being an emerging economy. Rajwani and Mukherjee (2013) studied Indian stock market's connectedness with other Asian stock markets and found that Indian stock market is not connected with any of the Asian stock markets, which shows insensitivity of Indian stock markets with other markets.…”
Section: Ijoes 351mentioning
confidence: 99%
“…It was seen in his paper that shocks in US had impact on Bangladesh, being an emerging economy. Rajwani and Mukherjee (2013) studied Indian stock market's connectedness with other Asian stock markets and found that Indian stock market is not connected with any of the Asian stock markets, which shows insensitivity of Indian stock markets with other markets.…”
Section: Ijoes 351mentioning
confidence: 99%
“…Hence, it is important to carry out further researches in order to understand the definite behavior of Asian markets. The more so as the markets of this range react differently to changes, they are not equally integrated, what is highlighted by crises (Singhania, Anchalia 2013;Rajwani, Mukherjee 2013;Seth, Sharma 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The study recommends portfolio diversification among the stock exchange of BRICS. Similarly, Rajwani and Mukherjee (2013) reported that Indian stock market is not co-integrated with any of the selected Asian stock market in long run. The study analyzed the secondary data of China, Japan, Malaysia, South Korea, Indonesia and Taiwan and reported that diversification can minimize the portfolio risk.…”
Section: Literature Reviewmentioning
confidence: 99%